Deep freeze [large type] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Virgil Flowers novels, 2017)
"Virgil knows the town of Trippton, Minnesota, a little too well. A few years back, he investigated the corrupt -- and as it turned out, homicidal -- local school board, and now the town's back in view with more alarming news: A woman's been found dead, frozen in a block of ice. There's a possibility that it might be connected to a high school class of twenty years ago that has a mid-winter reunion coming up, and so, wrapping his coat a little tighter, Virgil begins to dig into twenty years' worth of traumas, feuds, and bad blood. In the process, one thing becomes increasingly clear to him. It's true what they say: high school is murder." --